2022
DOI: 10.35971/jjhsr.v4i1.12248
|View full text |Cite
|
Sign up to set email alerts
|

Airport Noise Level and Its Effect on Blood Pressure on the Gorontalo Community

Abstract: The rapidly increasing flight activity affects the health of the population living, traveling, and working around or at airports. Noise generated by aircraft causes physiological and psychological disturbances. This study aims to assess the effect of noise on increasing blood pressure. The research was conducted in Tolotio Village, Gorontalo Regency in 2019. Respondents were selected using a purposive sampling technique. The Noise was collected using a Sound Level Meter, and blood pressure was collected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As previously discussed, recent research has shown that traffic noise has a significant impact on daily life comfort and can affect both the mental and physical health of individuals. Consequently, a considerable amount of research has been conducted to assess noise levels, inhabitants' perception, and measures for soundproofing and noise reduction in various settings, such as wind farms [18,19], schools [20], hypermarket [21], university community [22], metro trains and stations [23][24][25], airports [26,27], office buildings [28], and gyms [29]. Regarding the impact of traffic noise, recent studies have shed light on the various negative effects it has on residents' health and well-being, especially in the context of urban expressways.…”
Section: Related Workmentioning
confidence: 99%
“…As previously discussed, recent research has shown that traffic noise has a significant impact on daily life comfort and can affect both the mental and physical health of individuals. Consequently, a considerable amount of research has been conducted to assess noise levels, inhabitants' perception, and measures for soundproofing and noise reduction in various settings, such as wind farms [18,19], schools [20], hypermarket [21], university community [22], metro trains and stations [23][24][25], airports [26,27], office buildings [28], and gyms [29]. Regarding the impact of traffic noise, recent studies have shed light on the various negative effects it has on residents' health and well-being, especially in the context of urban expressways.…”
Section: Related Workmentioning
confidence: 99%